Pengaruh Metode Bernyanyi Dalam Peningkatan Penguasaan Mufradat - Yaziyah Della Puspita; Puspita, Yaziyah Della; LIza, Fitri (Jurnal Internasional Pendidikan Bahasa Arab, 2025)
In Arabic language learning, a pedagogically effective approach is required, one that not only incorporates technical proficiency but also engages students' emotional and cognitive domains to enhance vocabulary acquisition more optimally. This study examines the singing method based on Roger W. Sperry's theory that involves the functions of the right and left brain, potentially increasing vocabulary acquisition. The study used a one group pretest-posttest experimental design with two classes at SMP Muhammadiyah 35 Jakarta. Data were analyzed using normality tests, homogeneity tests, paired sample tests, independent sample tests, and N-Gain scores to measure the effectiveness of the singing method. The findings indicated that the implementation of the singing method led to a significant improvement in students' vocabulary mastery with the N-Gain score of the experimental class in the medium category (0.6034) and the control class in the low category (0.3073). This result shows that student emotions and cognitive abilities can both be stimulated by this strategy at the same time. In order to improve comfort, emotional involvement, and overall vocabulary acquisition effectiveness, teachers are advised to use song in language teaching.